Age at hip or knee joint replacement surgery predicts likelihood of revision surgery - Wainwright, C.; Theis, J.; Garneti, N.; Melloh, Markus (2011)
We compared revision and mortality rates of 4668 patients undergoing primary total hip and knee replacement between 1989 and 2007 at a University Hospital in New Zealand. The mean age at the time of surgery was 69 years (16 to 100). A total of 1175 patients (25%) had died at follow-up at a mean of ten years post-operatively. The mean age of those who died within ten years of surgery was 74.4 years (29 to 97) at time of surgery. No change in comorbidity score or age of the patients receiving joint replacement was noted during the study period. No association of revision or death could be proven with higher comorbidity scoring, grade of surgeon, or patient gender. We found that patients younger than 50 years at the time of surgery have a greater chance of requiring a revision than of dying, those around 58 years of age have a 50:50 chance of needing a revision, and in those older than 62 years the prosthesis will normally outlast the patient. Patients over 77 years old have a greater than 90% chance of dying than requiring a revision whereas those around 47 years are on average twice as likely to require a revision than die. This information can be used to rationalise the need for long-term surveillance and during the informed consent process. © 2011 British Editorial Society of Bone and Joint Surgery.